Peripapillary and Macular Flow Changes in Nonarteritic Anterior Ischemic Optic Neuropathy (NAION) by Optical Coherence Tomography Angiography (OCT-A) - Juejun Liu; Changzheng Chen; Lu Li; Zuohuizi Yi; Hongmei Zheng (Journal of Ophthalmology)
Background. To analyze the blood flow changes of radial peripapillary capillaries (RPCs) and macula with time procession in patients with nonarteritic anterior ischemic optic neuropathy (NAION) by optical coherence tomography angiography (OCT-A). Methods. A total of 21 affected eyes and 19 unaffected eyes from 21 NAION patients were included. Assessments of BCVA, CFP, SD-OCT, and OCT-A were performed on NAION patients at enrollment and at 1-2 weeks, 1-2 months, and 3–6 months after enrollment. Measures of the thickness of the peripapillary retinal nerve fiber layer (wRNFL) and macular ganglion cell complex (wGCC) of the whole image in SD-OCT, vessel density of the RPC (wRPC) and superficial and deep vascular complexes (wSVD, wDVD) in the whole image of OCT-A, and their superior- and inferior-hemi values (s/iRNFL, s/iGCC, s/iRPC, and s/iSVD) were assessed. Results. Compared to unaffected control eyes, wRPC (p≤0.001) was significantly lower in affected eyes at baseline, and there was no significant difference in wSVD (p>0.05). The wRPC and wSVD values of affected eyes were significantly decreased at follow-up time points of 1–2 and 3–6 months compared to baseline (p=0.001, p≤0.001; p≤0.001, p≤0.001). The sRPC values were significantly lower than iRPC at 1-2/3–6 months (p=0.016, p=0.013), and sSVD values were lower than iSVD at 1-2 months (p=0.010). Statistically significant correlations were found between wRPC and wRNFL values at 3–6 months (r = 0.626, p=0.022), between wSVD and wGCC at 1-2 weeks and 1-2 months (r = 0.570, r = 0.436; p=0.007, p=0.048). Conclusion. OCT-A revealed a sectorial reduction in vessel density in the RPC and macula with the disease progression of NAION from acute to atrophic stages, a classification associated with structural deficits.